Analisis Potensi, Efektivitas, dan Kontribusi Pajak Rumah Kost terhadap Pajak Daerah di Kota Banjarmasin - Siti Sarah Sairatin; Lina Suherty (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This study aimed to determine the potential, effectiveness, and contribution of boarding house tax in Banjarmasin. This type of research is quantitative descriptive research. The population in this study are all boarding house businesses registered as taxpayers in Banjarmasin City, with a sample of 65 taxpayers. The study was conducted by distributing questionnaires to boarding house business owners registered as taxpayers in Banjarmasin.The results showed a potential boarding tax of Rp 915,984,000. The level of effectiveness of boarding tax is very effective, where its achievement always exceeds 100% every year. However, the level of boarding tax contribution to local taxes is very less. Some internal factors such as lack of socialization and firmness of the government to control, socializing about the importance of registering boarding house businesses as taxpayers, and disciplining any taxpayer who is lazy to pay taxes, as well as external factors, namely lack of awareness of taxpayers to register boarding house businesses they are registered, taxpayers.